Screening Incarcerated Women for Opioid Use Disorder - Staton, Michele (Journal of drug issues, 2024)
The overall aim of the present study is to examine the utility of the DSM OUD Checklist and the NM-ASSIST screening tools to identify symptoms consistent with OUD among incarcerated women in county jails. This study contributes to the existing literature because research on screening and assessment approaches for incarcerated women has been limited. The focus of the current study is to describe the screening procedures and study recruitment for a larger parent study focused on increasing treatment linkages. Study findings indicate a positive correlation between indicators of OUD using the two screening tools, as well as a high degree of correlation between street opioid misuse and other high-risk drug indicators (overdose and injection practices). These findings underscore the importance of outreach, screening, and intervention in real-world settings, including jails, in order to increase access to OUD treatment among this vulnerable sample of women.